Comparative Study of Vitamin C on Serum Lipid Profile in Healthy Male and Female Human Subjects (Journal of Scientific Research, 2012)
This study aims to assess the comparative effects of vitamin C supplementation on lipid profiles in male and female human subjects. A total of 60 healthy individuals (male and female) were selected randomly, instructed and given the understanding of the purpose of study. The test group comprising  30 individuals  were given 500mg vitamin C tablets one daily for 30 days and control group of 30 individuals were given placebo capsules(glucose 500mg)  one daily for 30 days. Fasting blood samples were collected in the morning for estimation of cholesterol, triglycerides, HDL-C, LDL-C and VLDL-C on first day of the commencement of the study and second blood samples were taken after thirty days of supplementation and same estimations were carried out. Vitamin C caused reduction in serum total cholesterol and LDL cholesterol significantly but it did not have any statistically significant effect on HDL-C, VLDL-C and triglycerides. As far as gender is concerned the effect of vitamin C on lipid profile in males was not significantly different from those in females.© 2012 JSR Publications. ISSN: 2070-0237 (Print); 2070-0245 (Online). All rights reserved.doi: http://dx.doi.org/10.3329/jsr.v4i3.8894 J. Sci. Res. 4 (3), 775-781 (2012)